Use of Digital Technology to Support the Entrepreneurship Education Process - Sulistianingsih Sulistianingsih (Indo-MathEdu Intellectuals Journal, 2023)
Entrepreneurship education is an important part of preparing individuals to develop the insights, skills, and attitudes needed to create and manage successful business ventures. This research aims to examine more deeply the use of digital technology to support the entrepreneurship education process. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and text from special sources, namely Google Scholar and Google search engine. The study results show that the use of digital technology in entrepreneurship education has brought fundamental changes in the way students learn, interact and prepare themselves to become successful entrepreneurs. From easy access to information to virtual business simulations, global collaboration to digital marketing, technology has become a driving force in changing the approach to entrepreneurship education